The Generatıonal Dıvısıon of Warfare and Controversıal Issues - Nuri Najafov, Zafar (Social Development and Security, 2025)
Purpose. To identify the transformational trends and controversial points of the changing face of military violence in the context of the concept of “Generations of warfare”.Method. Historical, comparative analysis, systematic approach, and structural analysis methods.Findings. Although the concept of “Generations of warfare” allows for a systematic study of the transformations from the classical to the hybrid form of military violence, and for the identification of the specific developmental determinants of different conflict generations, it should not be considered perfect. The incompleteness of generations of warfare, the lack of fundamental differences between some generations, is considered a new challenge to this concept.Theoretical implications. The concept of “Generations of warfare”, put forward by Lind in 1989, does not keep pace with modern military developments and armed conflicts, the concept of “generations of warfare” is not defined by clear boundaries. This theory is unable to explain the subsequent transformation of methods and means of military operations, the decisive impact of non-kinetic means – drones, artificial intelligence and cyberattacks – on military skill, as well as the essence of technology-based cyberwarfare and hybrid wars. This gap has been filled in the study of 5th generation warfare.Practical implications. The concept of “Generations of warfare” has had a significant impact on the improvement of combat equipment, the emergence of new tactics, and the transformation of military skills. With the help of the concept of “Generations of warfare”, practitioners can study the dynamics of military and military-practical transformations that have marked a huge period in human history, from the classical form of military violence to the hybrid form and become familiar with the shortcomings in this direction.Value. This article aims to study the dominant strategies and technologies of each generation of warfare in the context of the concept of “Generations of Warfare”, to explain the problematic aspects and to improve it in accordance with the requirements of new transformations.